Токсическое влияние тяжелых металлов на организм гидробионтов = Toxic effects of heavy metals on the hydrobionts' organism - M. R. Vergolyas; V. V. Goncharuk (Kazimierz Wielki University, 2016)
Vergolyas M. R., Goncharuk V. V. Токсическое влияние тяжелых металлов на организм гидробионтов = Toxic effects of heavy metals on the hydrobionts' organism. Journal of Education, Health and Sport. 2016;6(6):436-444. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56065 http://ojs.ukw.edu.pl/index.php/johs/article/view/3616   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016.   УДК 574.64:576.08:57.084.1   ТОКСИЧЕСКОЕ ВЛИЯНИЕ ТЯЖЕЛЫХ МЕТАЛЛОВ НА ОРГАНИЗМ ГИДРОБИОНТОВ   М. Р. Верголяс, В. В. Гончарук   Институт коллоидной химии и химии воды им. А. В. Думанского НАН Украины, г.Киев   Реферат Проведено биотестирование для оценки качества питьевых вод содержащих тяжелые металлы согласно по требованиям ГСанПиН 2.2.4-171-10, где значения ПДК (предельная допустимая концентрация) в питьевой воде свинца (Pb) 0,03 мг/дм3, железа (Fe) 0,3 мг/дм3 и марганца (Mn) 0,1 мг/дм3. Контрольную воду приготовили в лабораторных условиях согласно рекомендациям ДСТУ 4174:2003, которая соответствует показателям ГСанПиН 2.2.4-171-10. Для оценки влияния токсичности водных образцов использовали тест-организмы - гидры, Hydra attenuate, дафнии Ceriodaphnia affinis, рыбы Danio rerio и шпорцевые лягушки Xenopus культивированных в лабораторных условиях. Метод заключается в определении действия токсикантов на выбранные организмы в стандартных условиях с регистрацией изменений на поведенческих, физиологических и клеточном уровнях. Физико-химические методы определяют лишь наличие и количество химических элементов в тестируемых водных образцах, но не могут определить специфику формирования качества тестируемых водных образцах. Причиной этому является увеличение количества комбинаций химических соединений в водной среде (более 75 млн.). В качестве оптимального набора для определения некоторых структурных и функциональных изменений генома клетки вследствие токсического воздействия предложен микроядерный тест. Реакция тест-организмов рыб и лягушек на раздражение токсического характера проявляется в образовании микроядер в эритроцитах периферической крови. Показана перспективность использования тест-организмов для оценки качества водной среды. Особое внимание уделено оценке риска для здоровья человека токсических веществ в питьевой воде, генотоксичность и цитотоксичность, которых выявляются с помощью гематологических показателей животных клеток. Универсальность клеточной организации открывает широкие возможности для токсикологических исследований с применением периферической крови различных групп животных (рыбы, лягушки) и последующей экстраполяцией полученных результатов на клетки крови и организм человека. Ключевые слова: токсичность, генотоксичность, биотестирование, токсиканты, питьевая вода.   TOXIC EFFECTS OF HEAVY METALS ON THE HYDROBIONTS' ORGANISM M. R. Vergolyas, V. V. Goncharuk Institute of colloid chemistry and water chemistry named A. V. Dumansky NAS Ukraine, Kyiv, Ukraine   Abstract A bioassay for evaluating the quality of drinking water containing heavy metals, according to the requirements by GSanPiN 2.2.4-171-10 where the MAC value (maximum permissible concentration) in the drinking water of lead (Pb) 0,03 mg / dm3, iron (Fe) 0,3 mg / dm3 and manganese (Mn) 0,1 mg / dm3. The control water is prepared in the laboratory according to the recommendations of the State Standard 4174: 2003, which corresponds to parameters GSanPiN 2.2.4-171-10. To evaluate the effect of water samples toxicity using the test organism - hydra, Hydra attenuate, fleas Ceriodaphnia affinis, fish Danio rerio and Xenopus Xenopus cultured in the laboratory. The method consists in determining the actions of toxicants on selected organisms under standard conditions with registration changes in the behavioral, physiological, and cellular levels. Physicochemical methods only determine the presence and amount of chemical elements in the test water samples, but can not determine the specificity of formation water quality test samples. The reason for this is to increase the number of combinations of chemical compounds in an aqueous medium (more than 75 Mill.). As an optimal set for the determination of some of the structural and functional changes in the genome of the cells due to the toxic effects of proposed micronucleus test. The reaction of the test organisms, fish and frogs to the irritation of the toxic nature manifests itself in the formation of micronuclei in red blood cells of peripheral blood. The prospects of the use of the test organisms for evaluating the quality of the aquatic environment. Particular attention is given to the evaluation of toxic substances to human health risk of drinking water, genotoxicity and cytotoxicity, which are detected by hematological parameters of animal cells. The versatility of cellular organization opens up opportunities for toxicological studies using peripheral blood of different groups of animals (fish, frogs) and subsequent extrapolation of the results to the blood cells and the human body. Keywords: toxicity, genotoxicity, bioassay, toxicants, drinking water.